2015
DOI: 10.2169/internalmedicine.54.3845
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Distribution of Capsular Serotypes of <i>Streptococcus pneumoniae</i> Isolated from Adult Respiratory Specimens in Japan

Abstract: Objective The objective of this study was to assess whether the distribution of pneumococcal capsular types has been changed, while also providing basic data on changes in the distribution after the introduction of Pneumococcal conjugated vaccine (PCV)13 in adult medical practice. Methods We analyzed 431 Streptococcus pneumoniae strains (200 in 2006 and 231 in 2012) that had been isolated from respiratory infection specimens from adult patients. Capsular typing was performed by the Quellung reaction and multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
(9 reference statements)
0
6
0
Order By: Relevance
“…Using 5 major databases, we comprehensively conducted systematic literature survey to identify studies that reported on the serotype distribution of adult pneumococcal pneumonia. In our pooled data analysis of the 4 studies (1,(17)(18)(19), the proportion of PCV7-covered serotypes decreased significantly and the proportions of serotypes of PCV13-PCV7, PPV23-PCV7, PPV23-PCV13, and non-VTs increased significantly. In summary, the decrease of the proportion of PCV7-covered serotype led to the increase of the proportion of non-PCV7-covered strains.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…Using 5 major databases, we comprehensively conducted systematic literature survey to identify studies that reported on the serotype distribution of adult pneumococcal pneumonia. In our pooled data analysis of the 4 studies (1,(17)(18)(19), the proportion of PCV7-covered serotypes decreased significantly and the proportions of serotypes of PCV13-PCV7, PPV23-PCV7, PPV23-PCV13, and non-VTs increased significantly. In summary, the decrease of the proportion of PCV7-covered serotype led to the increase of the proportion of non-PCV7-covered strains.…”
Section: Discussionmentioning
confidence: 73%
“…Second, there was some heterogeneity between each study in the pooled analysis regarding the diagnostic criteria, differentiation of 6A 6C, and target disease (i.e., including CAP, health care-associated pneumonia, or all LRTI). Particularly, 100 non-pneumonia LRTI cases included in the study by Shoji et al (17) might have influenced our results. We therefore conducted a sensitivity analysis excluding the study by Shoji et al and found that the pooled estimates were almost identical to the primary analysis.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The current polysaccharide-based multivalent vaccines induce protective immunity against and suppress infections due to S. pneumoniae isolates of the same serotypes as the vaccine antigens and not other serotypes. 18 - 21 In this way, the current multivalent vaccine promotes a vicious cycle of pneumococcal serotype replacement. To overcome this problem, vaccines containing one or more universal antigens that are expressed by all serotypes of S. pneumoniae and thus induce protection against all isolates of S. pneumoniae are desired.…”
Section: Development Of a Nanogel-based Nasal Vaccine Against Pneumoniamentioning
confidence: 99%